2021
DOI: 10.1093/jphsr/rmab067
|View full text |Cite
|
Sign up to set email alerts
|

Are pharmacists well equipped to deal with global health emergencies? Burnout during COVID-19

Abstract: Objectives This study aimed to evaluate and assess the burnout effect among pharmacists during COVID-19 pandemic in Kuwait. Methods A cross-sectional study using an online self-administered questionnaire was conducted from September 2020 to January 2021. The questionnaire included demographic questions as well as items from the Copenhagen Burnout Inventory (CBI) to assess burnout in three domains: personal burnout, work-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Studies showed the undesirable effect of health workers turnover on health systems, such as the increase in costs, 18,22,23 reduced staff productivity, 22 increased hospitalization rates, 23 and decreased quality of care. 7,24 Several healthcare workers suffered from professional burnout during and after the COVID-19 pandemic, 6,9,25,26 which also increased health workers turnover. 25,27 -30…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies showed the undesirable effect of health workers turnover on health systems, such as the increase in costs, 18,22,23 reduced staff productivity, 22 increased hospitalization rates, 23 and decreased quality of care. 7,24 Several healthcare workers suffered from professional burnout during and after the COVID-19 pandemic, 6,9,25,26 which also increased health workers turnover. 25,27 -30…”
Section: Introductionmentioning
confidence: 99%
“…Several studies documented the existence of professional burnout among health workers. [3][4][5][6][7] Professional burnout was found among different workers' categories, 4,8,9 settings or specialties, 5,6,10 and different stages of their careers. [11][12][13] Professional burnout can have several negative mental and psychological consequences, such as depression, 8,14 and adverse physical effects, such as cardiovascular disorders, musculoskeletal complaints, prolonged fatigue, and headaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation